1997
DOI: 10.1002/(sici)1097-0215(19970529)71:5<900::aid-ijc32>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversal activity of cyclosporin A and its metabolites M1, M17 and M21 in multidrug-resistant cells

Abstract: Cyclosporin A (CSA) is an effective inhibitor of the P-glycoprotein (P-gp) activity and has been shown to modulate multidrug resistance (MDR) in in vitro experimental models. During degradation of CSA, the metabolites arising from the parental compound reach high levels in the serum of patients, and it is not clear whether these metabolites maintain the reversal activity of the parental compound, like the metabolites of verapamil. In an in vitro experimental model, we compared the reversal activity of CSA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…27,28 However, the effect of CsA in MCF-7 has been barely considered in previously studies as far as we know. We found that CsA could also profoundly increase the DOX level in MCF-7 (1.3-fold), thus indicating the effect of P-gps on chemotherapy.…”
mentioning
confidence: 99%
“…27,28 However, the effect of CsA in MCF-7 has been barely considered in previously studies as far as we know. We found that CsA could also profoundly increase the DOX level in MCF-7 (1.3-fold), thus indicating the effect of P-gps on chemotherapy.…”
mentioning
confidence: 99%
“…④ Increasing the conversion of CsA to M17 and other metabolites. The immunosuppressive effect of M17 was same as that of CsA, and its renal toxicity was significant less[16],[25],[26].…”
Section: Discussionmentioning
confidence: 77%